2004
DOI: 10.1097/01.aog.0000142712.80407.fd
|View full text |Cite
|
Sign up to set email alerts
|

Decline of Serum Human Chorionic Gonadotropin and Spontaneous Complete Abortion: Defining the Normal Curve

Abstract: The rate of hCG decrease in spontaneous abortions is described by a quadratic profile, with a faster decline in hCG value with higher presentation levels. A rate of decline less than 21% at 2 days or 60% at 7 days suggests retained trophoblasts or an ectopic pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 13 publications
3
77
0
Order By: Relevance
“…Barnhart et al (2004) and Fong et al (2005) revealed that there is a relationship between early pregnancy outcome and β-hCG levels. 27,28 Forat et al (2007) examined the relationship between long-term pregnancy outcome and hCG.…”
Section: Discussionmentioning
confidence: 99%
“…Barnhart et al (2004) and Fong et al (2005) revealed that there is a relationship between early pregnancy outcome and β-hCG levels. 27,28 Forat et al (2007) examined the relationship between long-term pregnancy outcome and hCG.…”
Section: Discussionmentioning
confidence: 99%
“…When using an HCG ratio (HCG at 48 h/ HCG at 0 h) cut-off of 0.87, the sensitivity and specificity for the prediction of failing Pregnancy of unknown locations were 92.7 and 96.7%, respectively (Condous., 2006.). A rate of decline in serum HCG 21% could define spontaneous resolution of the pregnancy of unknown locations (Barnhart et al, 2004.). Serial quantitative HCG, however, could not meet the rapid diagnosis of EPs.…”
Section: Prospective Analysismentioning
confidence: 99%
“…Barhart et al (11) studied the hCG serum levels in patients diagnosed with PUL and the final outcome of viable intrauterine pregnancy. In their study, the median hCG level at the time of application was reported as 388 and the average increase in the hCG levels was reported as 50% for the first day and 124% for the second day.…”
Section: Serum Hcg Levels In Early Viable Intrauterine Pregnancymentioning
confidence: 99%
“…If the level of the first serum hCG level is high, it would decline more rapidly. The time required for hCG levels to clear following dilation and curettage is generally between 12 and 16 days (11). When a spontaneously resolving pregnancy has serum hCG levels declining to undetectable levels without surgical or medical intervention, this is defined as a failed PUL.…”
Section: Serum Hcg Levels In Spontaneous Abortionmentioning
confidence: 99%